Konstruksi Nilai-Nilai Moral dalam Film Dancing In The Rain - Ana Pertiwi; Arfan; Sandi Muspika (Journal of Religion and Film, 2022)
This study examines the Film Dancing In The Rain produced by Screenplay Films Legacy Pictures which tells the life of an autistic child who gets discriminated against from the surrounding environment. The purpose of the study was to examine the moral message contained in Dancing In The Rain using Roland Barthes' Semiotic Analysis. Researchers specifically examined how the background to the emergence of Dancing In The Rain, how semiotics analysis of Dancing In The Rain, and what are the moral messages in Dancing In The Rain. This study uses qualitative methods by researching film series and audience responses. The data collection techniques used are observation, interview, and documentation. The results of this study show that the background of the emergence of Dancing In The Rain is the idea of the screenwriter to make a humanist film so that the audience can see that we are not perfect or surrounded by imperfect people and in order to better appreciate imperfections. The study also found pieces of the scene that had a moral message that the authors of the analysis used Roland Barthes Semiotics Analysis. The meaning of the denotations, connotations, and myths of the film has been mentioned in the chapter's findings. The moral message contained in this film is 3, namely the message of friendship, the message of non-discrimination that is how the life of autistic children is treated in society, and the message of sincerity and sincerity in friendship.